Os proscritos de Dyonelio Machado - Raabe, Camilo Mattar (2014)
The objective of the present study is the edition of an inedited romance of Dyonelio Machado, based on the manuscript present in DELFOS Espaço de Documentação e Memória Cultural, ignored by the editors because of the censure his author´s suffered against his esthetical and ideological ideas. Written in the year of the military dictatorship instauration in Brasil, 1964, Proscritos is the second volume of the trilogy Osflagelantes, with the first volume, Endiabrados, published in 1980 and winner of PrêmioJabuti, twenty years after written. First is developed an introductory study about Dyonelio Machado s life and the work, aiming to elucidate the difficulties he found to be published and accepted by the public, involving esthetical and ideological aspects. In a second moment, it will be specified the plan for the edition, based on textual criticism, focusing the procedures to fix the text and to prepare de facsimile edition, both presented in the end of the work.